2011
DOI: 10.1111/j.1399-0012.2011.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplements lower bone resorption after renal transplant

Abstract: Calcium malabsorption is prevalent in RT recipients, contributing to bone destruction and compounded by poor dietary intake and low 25(OH)D. Calcium supplementation appears to help overcome this deficiency and acutely suppress PTH. Calcium may be an effective and inexpensive therapy for bone loss in RT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…With the aim to reduce fracture risk after kidney transplantation, this study identified a new risk factor represented by pHPT, which may better select recipients who could benefit from treatment. Better control of hyperparathyroidism after kidney transplantation should be considered in some patients using efficient treatments, such as calcium supplementation , native and active vitamin D, cinacalcet and parathyroidectomy. Previous studies suggest a bone protective effect of cinacalcet in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim to reduce fracture risk after kidney transplantation, this study identified a new risk factor represented by pHPT, which may better select recipients who could benefit from treatment. Better control of hyperparathyroidism after kidney transplantation should be considered in some patients using efficient treatments, such as calcium supplementation , native and active vitamin D, cinacalcet and parathyroidectomy. Previous studies suggest a bone protective effect of cinacalcet in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…This postrenal transplant hyperparathyroidism could be treated with a calcimimetic or parathyroidectomy, although posttransplant parathyroidectomy may decrease renal transplant function as PTH has a known positive regulatory effect on renal perfusion and glomerular filtration rate [ 10 , 11 ]. We have recently shown that posttransplantation oral calcium therapy is an effective treatment for suppression of PTH [ 12 ]. In this study, we aimed to determine the prevalence of hypercalcaemia and to evaluate the risk factors for postrenal transplant hypercalcaemia in long-term renal transplant patients at our centre.…”
Section: Introductionmentioning
confidence: 99%
“…However, more solid data are needed to confirm this and to set the optimal level of serum Vitamin D supplementation in order to attain the best clinical outcome [92]. Calcium supplementation (500 mg elemental calcium daily) appears to lower bone resorption after transplantation and should be routinely prescribed—especially in regimens with high doses of immunosuppressive drugs [93]. Calcium dietary intake of at least 1 g daily should also be advised.…”
Section: Bone Diseases Following Pancreas Transplantationmentioning
confidence: 99%